Scientific culture, academic writing and our students. Opening of the section of articles written by students of the University of Guayaquil. - Viteri Briones, Telmo (Revista Universidad de Guayaquil, 2015)
Formative research should be a priority in university education. Its pertinence is undeniable to link higher education with the needs of society. It’s imperative that the educational teaching process would be accomplished through the development of research skills in such a way that the modes of action of the pedagogical mediator in the classroom, allows his work to be more effective by interweaving the theoretical and practical. The professor-researcher transforms and evolves his knowledge in order to find solutions to the problems of the profession and learning; but also involves the student in that praxis that generates genuine habits and research skills, gets autonomy in the complex path, brings him closer to the reflection of the great and everyday difficulties mm of the world in which he lives and allows him to perform a cognitive-metacognitive-attitudinal assessment of his theoretical constructs and develops cultural and educational scientificity from both.
Keywords: Formative Research Skills; theoretical general intellectual skills; scientific and technological research; formative assessment